The threat of IS proxy warfare on Indonesian Millennial Muslims - M Affan (Indonesian Journal of Islam and Muslim Societies, 2018)
So far, terrorism tends to be considered using asymmetric warfare methods rather than proxy warfare methods. Even though some terror attacks around the world carried out by people inspired by terrorism indicate that terrorist groups such as IS are carrying out proxy warfare methods. Based on this problem, the following article will describe the threat of IS terrorism through proxy warfare. The aims of this research to map the threat of IS proxy warfare on Indonesian Millennial Muslims. By using library research methods, this research is expected to have positive implications for the efforts to deradicalize terrorism among Indonesian Millennial Muslims. The conclusion of this research obtained shows that the advancement of communication technology has facilitated IS to spread its terrorism in Indonesia through online magazine propaganda in Bahasa Indonesia. This effort is really a threat for Indonesian Millennial Muslims who are very active in using the internet daily. In this way, IS seeks to influence Indonesian Millennial Muslims to become their proxy in running nikayah operations independently. Thus, the threat of terrorism throughout the world has also evolved from the threat of asymmetric warfare to the threat of proxy warfare, especially to Millennial Muslims.Sampai sejauh ini, terorisme cenderung dianggap menggunakan metode peperangan asimetris daripada peperangan proksi. Meski begitu, beberapa serangan teror di seluruh dunia yang dilakukan oleh orang-orang yang terinspirasi terorisme mengindikasikan bahwa kelompok teroris semacam IS sedangmenjalankan metode peperangan proksi. Berdasarkan permasalahan ini, artikelberikut akan menjelaskan ancaman terorisme IS melalui peperangan proksi.Tujuan dari penelitain ini adalah memetakan ancaman peperangan proksi ISpada Muslim Milenial Indonesia. Dengan menggunakan metode penelitianpustaka, penelitian ini diharapkan dapat berimplikasi positif pada usahaderadikalisasi terorisme pada Muslim Indonesia. Kesimpulan penelitian sendirimenunjukkan bahwa kemajuan teknologi komunikasi telah memfasilitasi ISuntuk menyebarkan terorisme di Indonesia melalui propaganda majalah daringdalam Bahasa Indonesia. Upaya ini benar-benar menjadi ancaman bagi MuslimMilenial Indonesia yang sangat aktif menggunakan internet setiap hari. Dengancara ini, IS berusaha mempengaruhi Muslim Milenial Indonesia untuk menjadiwakil mereka dalam menjalankan operasi nikayah secara mandiri. Dengandemikian, ancaman terorisme diseluruh dunia juga telah berevolusi dariancaman peperangan asimetris kepada ancaman peperangan proksi khususnyapada Muslim Milenial.